Penerapan Media Index Card Match dalam Keterampilan Menulis Teks Laporan Hasil Observasi pada Peserta Didik Kelas VIII SMPN 13 Kota Gorontalo Tahun Pelajaran 2024/2025: Penelitian - Karim Ahmad; Supriyadi; Salam (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe: (a) the implementation of Index Card Match media-based teaching modules in learning the skills of writing observation report texts, (b) the implementation of Index Card Match media in learning activities, and (c) student learning outcomes after the implementation of Index Card Match media in learning to write observation report texts. This study uses a qualitative descriptive approach with a natural observation type. The results of the study indicate that the implementation of open modules with the integration of Index Card Match media is systematically arranged by containing learning components that are in accordance with the Independent Curriculum. The implementation of Index Card Match media in learning shows positive results. During the activity, students looked enthusiastic and active in interacting with their peers. This is evidenced by the results of the final test which showed an average score of 72.63. This value shows that most students have achieved the Learning Objective Achievement Criteria (KKTP) in the Independent Curriculum because the independent curriculum no longer uses the term KKM or Minimum Completion Criteria set by the school.